2011
DOI: 10.1042/bsr20100065
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin regulates miR-21 expression and inhibits invasion and metastasis in colorectal cancer

Abstract: A c c e p t e d M a n u s c r i p tLicenced copy. Copying is not permitted, except with prior permission and as allowed by law. © 2010 The Authors Journal compilation © 2010 Portland Press Limited AbstractCurcumin has promising potential in cancer prevention and therapy by interacting with proteins and modifying their expression and activity, which includes transcription factors, inflammatory cytokines, and factors of cell survival, proliferation, and angiogenesis. miR-21 is overexpressed in many tumors, promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
213
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(224 citation statements)
references
References 50 publications
8
213
0
3
Order By: Relevance
“…Curcumin is the release of cytochrome c and stability of P53 [23]. Curcumin inhibits the transcriptional network in stages and thus prevents the cell proliferation [26]. In another study of cell cycle arrest and growth of curcumin on gastric cancer cells was observed [27].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is the release of cytochrome c and stability of P53 [23]. Curcumin inhibits the transcriptional network in stages and thus prevents the cell proliferation [26]. In another study of cell cycle arrest and growth of curcumin on gastric cancer cells was observed [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-186* is involved in curcumin-induced apoptosis in A549/ DDP multidrug-resistant human lung adenocarcinoma cells (Zhang et al, 2010). Downregulation of miR-21 transcription via activator protein 1 mediates the suppressive effects of curcumin on tumor growth, invasion and in vivo metastasis in colorectal cancer (Mudduluru et al, 2011). Induction of tumor suppressive miRNAs is another mechanism linked to the cytotoxicity of curcumin against cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…구강암 세포주에서는 curcumin이 notch-1과 NF-kB 신호 전달체계를 억제시킴으로써, 암세포의 성장을 저해하고 세포 사멸을 유도하는 것으로 보고 되었다 [10]. 또한, 대장암 세포주 모델에서는curcumin이 miR-21의 발현을 조절함으로써, 암세 포의 성장과 전이과정을 저해하는 것으로 보고되었다 [11]. 그 러나, 대장암 HCT116 (Fig.…”
Section: 서 론unclassified